Pengaruh Kualitas Produk dan Harga terhadap Keputusan Pembelian Produk Kosmetik Wardah - Dhina Osiska; Rizka Leonitha; Rosgita Rosgita; Eman Sulaeman (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to analyze the effect of product quality and price on the decision to purchase Wardah cosmetic products and analyze the variables that have the most dominant influence on purchasing decisions. The population in this study were consumers of Wardah cosmetic products in DKI Jakarta and West Java. In this study the sampling technique used was accidental sampling with a total of 73 respondents. The research method used is a survey method and this research approach uses a field research approach. This type of research is quantitative research. The data analysis tool used is multiple linear regression analysis with the help of SPSS 25 for windows to determine the effect of product quality and price on purchasing decisions for Wardah cosmetic products. The results showed that partially all the independent variables had an effect on the dependent variable. The influence of the two independent variables is positive and significant, meaning that the better the quality of the product and the more affordable the price offered, the higher the purchase decision made by consumers.